Strategi Pengembangan Manajemen Pengelolaan Pusat Kegiatan Belajar Masyarakat (PKBM) di Provinsi Riau - Emma Himayaturohmah (UHN IGB Sugriwa Denpasar, 2017)
Community Learning Center (CLC) is a non-formal education institution that serves as a place and opportunity for the community members to learn. CLC develops as learners’ needs, educational regulations, and general society develop. The implementation of learning activities differs from one CLC to another. The quality also varies between one CLC institution and the next. The quality of human resources in CLC contributes to the quality of the CLC. The key human resource that plays a great role in determining the success or failure of CLC is its manager. Managerial ability of CLC managers is one of the key factors of CLC’s success. To improve the quality of CLC, the quality of its managers has to be improved first. CLC managers have to possess sufficient knowledge, skills, and capabilities to realize the nine characters of CLC set in the Standard and Operational Procedures of CLC. Nowadays, CLC faces several problems in quality improvement: (1) whether or not the developed learning programs are oriented towards the learners and stakeholders; (2) whether or not all stakeholders of CLC are actively involved in the management and development of CLC; (3) whether or not learning implementation and evaluation been performed as required; it is unlikely that CLC will meet the quality standard set by the community without first having a tool to measure its progress and achievement; (4) whether or not all interested parties have strong commitment to quality improvement; and (5) whether or not the improvement and development efforts in CLC management and learning implementation have been continuous and sustainable. One of the quality improvement efforts in CLC is the development of managerial professionalism. The managers of CLC may implement CLC managerial development strategies, which begin with strategic planning. Managerial development strategies include effective and efficient management of resources and the implementation of skill development and public enrichment approaches.